Biogas production on dairy farms: A Croatia case study - Nikola Bilandžija; Neven Voća; Tajana Krička; Vanja Jurišić; Ana Matin (Mljekarstvo)
In order to determine the differences in the production and composition of biogas as well as the quality of digested residue from anaerobic digestion of the raw materials generated by dairy farms in Croatia, investigations were undertaken in the biogas laboratory facility of the Faculty of Agriculture. The investigated raw materials were: dairy manure, corn silage, haylage and equal-measure mix (1/3) of all raw materials. For each substrate, three runs of experiments were performed with the same overall hydraulic retention time (40 days) and temperature of digestion (35 °C) in mesophilic conditions. The investigations found that the most efficient production of biogas was from corn silage. As for biogas composition, it was acceptable in all investigated samples both in energy and environmental terms. Digested residues, which are mildly alkaline, have low dry matter content. About 70 % of dry matter content is organic. On the basis of N:P:K analysis and the analysis of biogenic elements values and heavy metal values, it can be concluded that digested residues of all input raw materials can be used in agricultural production.